Intertemporal preference reversals are associated with early activation of insula and sustained preferential processing of immediate rewards in visual cortex - Sathya Narayana Sharma; Azizuddin Khan (Scientific Reports, 2021)
Abstract Decision makers tend to give magnified significance to immediately available rewards which leads to intertemporal preference reversals, which is a form of self-control failure. The objective of the present study was to understand the cognitive and neural underpinnings of this phenomenon using event-related potentials (ERP) and their source localization using standardized low-resolution brain electromagnetic tomography analysis (sLORETA). Twenty-four participants performed a money choice task, where they made choices between a smaller-sooner and a larger-later reward, which included trials with and without an immediately available option, while their electroencephalography (EEG) activity was recorded. Trials with and without immediacy were identical except that the latter involved a front-end delay added to both the rewards. Results showed that presence of immediacy made the choices significantly more impulsive. Presence of immediate reward elicited larger visual P2 and late positive potential (LPP), indicating enhanced capture of automatic and sustained attention respectively, and smaller N2, indicative of diminished engagement of cognitive control processes. Source localization revealed increased activity in the visual cortex in the presence of immediacy, signifying higher valuation. Higher activation of areas of insula during P2—suggesting increased awareness of visceral signals—predicted larger impulsive preference reversals. The results suggest that presence of immediate reward biases the choice very early during the decision making process by precipitating visceral states that triggers approach behaviour, and highlight the need to adopt strategies like precommitment to counter the effect.